2022
DOI: 10.3390/jcm11247477
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in the Treatment of Osteoporosis and the Effects on Bone Healing

Abstract: Osteoporosis (OP) is a major global health concern, with aging being one of the most important risk factors. Osteoarthritis (OA) is also an age-related disorder. Patients with OP and/or OA may be treated surgically for fractures or when their quality of life is impaired. Poor bone quality due to OP can seriously complicate the stability of a bone fixation construct and/or surgical fracture treatment. This review summarizes the current knowledge on the pathophysiology of normal and osteoporotic bone healing, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 216 publications
0
12
0
1
Order By: Relevance
“…The medium age of the population is 50.0 and 50.81% were men. Most of the subjects were obese (median (interquartile range) BMI: 27.59 (24.15–31.47) kg/m 2 ]. Regarding the metabolic syndrome, though the blood pressure was not high (120.67 mm Hg of medium SBP, and 69.33 mm Hg of medium DBP when measured at participation), nearly half of the subjects has a hypertension history (40.14%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium age of the population is 50.0 and 50.81% were men. Most of the subjects were obese (median (interquartile range) BMI: 27.59 (24.15–31.47) kg/m 2 ]. Regarding the metabolic syndrome, though the blood pressure was not high (120.67 mm Hg of medium SBP, and 69.33 mm Hg of medium DBP when measured at participation), nearly half of the subjects has a hypertension history (40.14%).…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis, with the characteristics of declined bone mass and degraded bone microstructure, is considered a common senile disease that could lead to an increased risk of bone fragility and fracture, and contribute to an increased mortality in patients [ 1 ]. With an estimated 200 million people affected, osteoporosis has been a major global public health concern [ 2 ]. As an essential determinant of bone health, the measurement of bone mineral density (BMD) is a common operational tool for the diagnosis of osteoporosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, strontium-incorporated silica-based glass scaffolds can enhance bone regeneration by inhibiting osteoclast activity (Wei et al 2014). Excessive osteoclast activity during bone formation may lead to the impairment of physiological bone coupling and new osteoporotic bone (Kushchayeva et al 2022). Herein, we demonstrated that Zn- and F-releasing 4% Al-MP glass could suppress osteoclastogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The annual cost of osteoporosis fracture prevention and treatment in the United States is expected to exceed $50 billion 20 years from now (4,5). Investigation of risk factors for osteoporosis is an important tool for maintaining bone mass and reducing fracture risk (6). In addition to common laboratory and screening indicators (e.g., blood lipids, body composition, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of risk factors for osteoporosis is an important tool for maintaining bone mass and reducing fracture risk ( 6 ). In addition to common laboratory and screening indicators (e.g., blood lipids, body composition, etc.)…”
Section: Introductionmentioning
confidence: 99%